Optimization of Elephant Foot Yam (Amorphophallus Paeoniifolius) Extract Syrup Formula as a Nutritive Antioxidant Drink - PUTRI, Ineke; HINTONO, Antonius; SUSANTI, Siti (International Journal of Sustainable Agricultural Research, 2018)
Extract of Elephant Foot Yam (EFY) is known to contain flavonoid that is an antioxidant compound and thus has the potential to be utilized as functional food in the form of beverages. Functional drinks made from plants are usually presented as healthy drinks, which in this case is in the form of syrup. This study aims to determine the antioxidant activity, pH value, viscosity and sensory properties of EFY extract syrup with different extract formulas and find out which of the formulated syrup produced is best based on its antioxidant activity and physical characteristics. The syrups produced were derived from 3 different types of formulas determined which were F1 (0.6% extract), F2 (2% extract) and F3 (4% extract). The parameters observed in this study were antioxidant activity, pH value, viscosity, and sensory properties of the syrup. The results obtained show that variations of the extract concentration in the formula have effects on the antioxidant activity, pH value, viscosity, aroma, and consumers’ preference of the syrup. The syrup formula with a concentration of 4% extract (F3) was found to have favorable properties as it has the highest antioxidant activity of 71.39 ppm; pH value of 4.97; and viscosity 0.265 c. In terms of consumer’s preference, the syrup with 0.6% extract (F1) is most preferably in color, flavor, and aroma. Thus EFY potentially as antioxidant source that can be added into the healthy drink in the form of syrup.